Pengaruh Pembelajaran Kewirausahaan dan Motivasi terhadap Minat Untuk Berwirausaha Mahasiswa IKIP PGRI Jember - Roro Aditya Novi Wardhani, Suci Rachmawati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2019)
This Research was conducted to analyze and know whether there is an effect of the enter reneurship learning and enterpreneurial motivation on the enter reneurial interest of IKIP PGRI Jember students partially and simulta. This type of research was quantitative research. Primary data was collected thought questionnaires distributedto the students of IKIP PGRI Jember Economic education department at 2016 and 2017 academic year. The population of this research was 121 students. The sample of thisresearch was 40 respondents of the economic education department at 2016 and 2017 academic year. Hypothesis test used multiple linier regression analysis. Based on the results of the data analysis used t-test or partially that is between enterpreneurship learning obtained tcount (2,482) > ttable (2,021) with a significance of 0,018 so that there is an influence on student enterpreneurship interest. t-test data analysis or partially that is between enterpreneurial motivation obtained tcount (2,093) < ttable (2,021) with a significance of 2,093 so that there is an influence on student enterpreneurship interest. from the data analysis used f-test of simultareonly that is between enterpreneurship learning and enterpreneurial motivation.